Dickkopf-1 (DKK1) blockade mitigates osteogenesis imperfecta (OI) related bone disease - Jih-Yang Ko; Feng-Sheng Wang; Wei-Shiung Lian; Fu-Shine Yang; Jeng-Wei Chen; Po-Hua Huang; Chin-Yi Liao; Shu-Jui Kuo (Molecular Medicine, 2024)
Abstract Background The current treatment of osteogenesis imperfecta (OI) is imperfect. Our study thus delves into the potential of using Dickkopf-1 antisense (DKK1-AS) to treat OI. Methods We analysed serum DKK1 levels and their correlation with lumbar spine and hip T-scores in OI patients. Comparative analyses were conducted involving bone marrow stromal cells (BMSCs) and bone tissues from wild-type mice, untreated OI mice, and OI mice treated with DKK1-ASor DKK1-sense (DKK1-S). Results Significant inverse correlations were noted between serum DKK1 levels and lumbar spine (correlation coefficient = − 0.679, p = 0.043) as well as hip T-scores (correlation coefficient = − 0.689, p = 0.042) in OI patients. DKK1-AS improved bone mineral density (p = 0.002), trabecular bone volume/total volume fraction (p < 0.001), trabecular separation (p = 0.010), trabecular thickness (p = 0.001), trabecular number (p < 0.001), and cortical thickness (p < 0.001) in OI mice. DKK1-AS enhanced the transcription of collagen 1α1, osteocalcin, runx2, and osterix in BMSC from OI mice (all p < 0.001), resulting in a higher von Kossa-stained matrix area (p < 0.001) in ex vivo osteogenesis assays. DKK1-AS also reduced osteoclast numbers (p < 0.001), increased β-catenin and T-cell factor 4 immunostaining reactivity (both p < 0.001), enhanced mineral apposition rate and bone formation rate per bone surface (both p < 0.001), and decreased osteoclast area (p < 0.001) in OI mice. DKK1-AS upregulated osteoprotegerin and downregulated nuclear factor-kappa B ligand transcription (both p < 0.001). Bone tissues from OI mice treated with DKK1-AS exhibited significantly higher breaking force compared to untreated OI mice (p < 0.001). Conclusions Our study elucidates that DKK1-AS has the capability to enhance bone mechanical properties, restore the transcription of osteogenic genes, promote osteogenesis, and inhibit osteoclastogenesis in OI mice.